The increasing importance of Dengue virus infection in Saudi Arabia: A review - Ahmad M. Alharbi (Virus Research)
Exacerbated by the rise of global warming due to climate change, as well as ease of international travel and mass migration, the dengue virus infection remains of particular economic and global concern. Of note, the emergence of the first case of dengue viral infection occurred in Saudi Arabia in the 1990s, and since then there has been a steady rise in the number of cases. Moreover, the arrival of imported dengue virus variants poses a significant challenge to dengue fever surveillance and control efforts within the region, especially as Saudi Arabia attracts millions of religious pilgrims throughout the year. Herein, we discuss the epidemiology of dengue viral infection in Saudi Arabia, dengue fever biology and clinical manifestation. Current management strategies, amongst other factors influencing dengue fever in Saudi Arabia are also deliberated upon. Future ongoing research and consistent monitoring of both established and emerging dengue viral strains within Saudi Arabia are needed, given the lack of current comprehensive studies.